Protocol for evaluating the activity of R2 retrotransposons in mammalian cells - Yangcan Chen; Shengqiu Luo; Yanping Hu; Qi Zhou; Wei Li (STAR Protocols)
Summary: R2 retrotransposons can be harnessed to insert genes at targeted sites by all-RNA delivery, presenting a new technology for next-generation biotherapeutics. Here, we report a protocol for evaluating the gene integration activity of R2 retrotransposons in mammalian cells. We describe the construction of vectors separately expressing R2 protein and donor, the process of liposome transfection, and flow cytometry. This protocol provides a useful reporter system, which can be applied to evaluate the activity of other new retrotransposon systems.For complete details on the use and execution of this protocol, please refer to Chen et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.